Characteristics of radiology: Giant bullous emphisematous compare pneumothorax - Majdawati, Ana (Science Midwifery, 2025)
Background: Giant Bullous Emphysematous (GBE) or Vanishing Lung Syndrome is developed from bullous lung parenchyma diseases and can have multiple causes. The Images between GBE with pneumothorax are similar and difficult to differentiate bullae from pneumothorax. Case Presentations. A 27-year-old-man to emergency room with dyspnoea. Respiratory rate 32 and coarse upper breath sounds and diminished breath sounds in the right lung. Chest Computed Tomography (Chest CT) and Chest Smaller such bullous lesions are also seen in the left upper lobe. Discussion. Characteristics Chest CT and CXR GBE compare pneumothorax are: 1) the location of lesions: GBE contained within the lung and pneumothorax is collection of air in pleural space; 2) The shape of the lesions: GBE, oval, thin walled-less than 1 mm may be formed by pleura, septa or compressed lung tissue. Pneumothorax: with linear density outlining distinctive luscent area with bronchovascular markings are absent; 3) Complications: GBE caused minimal mediastinal line shifts and spontaneous pneumothorax. Pneumothorax with large areas caused greater mediastinal shift line. Summary. Chest CT and CXR are important to determine the diagnosis of GBE with pneumothorax: the location of lesions, The shape of the lesions and complications. They are important because both are cases of emergency that diagnosis can be implemented immediately so that handling can be rendered optimally.